2007
DOI: 10.1007/s00266-006-0151-3
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Volumetric Reduction for Masseteric Hypertrophy

Abstract: Masseteric hypertrophy occurs frequently among Asians, including Koreans, because of racial characteristics and dietary habits. It is thought to be an unpleasant feature, especially because of its strong and masculine impression. Recently, the authors developed a method for the volumetric reduction of hypertrophied masseter muscles using radiofrequency energy to correct the squared facial appearance caused by the hypertrophy. This study was performed to investigate the effects of radiofrequency applied to redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…It is fan‐shaped, and originates from the inferior margin and the medial surface of the zygomatic arch and ends on the lateral surface of the mandible. Masseteric hypertrophy is usually associated with mandibular angle prominence and inappropriate habits, such as clenching and bruxism . In 2001, von Lindern et al reported that BTA injection can reduce the masseter muscle's volume.…”
Section: Discussionmentioning
confidence: 99%
“…It is fan‐shaped, and originates from the inferior margin and the medial surface of the zygomatic arch and ends on the lateral surface of the mandible. Masseteric hypertrophy is usually associated with mandibular angle prominence and inappropriate habits, such as clenching and bruxism . In 2001, von Lindern et al reported that BTA injection can reduce the masseter muscle's volume.…”
Section: Discussionmentioning
confidence: 99%
“…Botulinum toxin A injection for the treatment of masseteric hypertrophy is popular due to the simplicity of the procedure and the rapid postoperative recovery times (6). In 2007, Jin Park et al first reported on the usage of RF ablation for the correction of masseteric hypertrophy in 340 patients and achieved favorable clinical results (3). To date, there have been no studies comparing the treatment and side effects of injection with botulinum toxin A with those of RF ablation for the treatment of masseteric hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…However, a previous study has reported that a mild injury to the facial nerve and parotid duct may occur postoperatively (3). In order to avoid parotid duct and facial nerve injury, in the present study, a new needle electrode was designed that reduced the amount of mucosal injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations